The effect of waste paper sludge ash (WPSA) as cementitious material to the properties of controlled low strength material (CLSM) containing recycled concrete aggregate (RCA) / Ahmad Najmi Fakhrudeen Mat Azmi - Mat Azmi, Ahmad Najmi Fakhrudeen (2017)
It is known that the construction industry, on a daily basis, uses quite a sum of natural resources to fulfil their occupational duties. Some examples to these resources are timber, cement, aggregate and water. Most of the aforementioned materials are nonrenewable and may decrease in the near future. However, there is an alternative to ensure lower usage of natural resources and that is to reuse current waste as a construction material. Evidently, certain waste materials can be used to reduce the usage of cement altogether. Waste Paper Sludge Ash, or in short, WPSA, happens to be one of the industrial wastes that has been in demand as of late. Reason being, it can be used as a replacement for cement due to its considerable high amounts of aluminosiliceous materials. WPSA also helps in reducing several problems on disposal. This research presents the results of a parametric study on the Controlled Low Strength Material (CLSM) using WPSA from a mill plant named MNI Mentakab in the state area of Pahang. Prior to this research, it has been expected that WPSA can serve as a cementitious material substituting cement and thus reducing the exploration of natural resources. The CLSM properties that have been investigated are divided into two properties which are; plastic properties and hardened properties. In plastic properties, several tests were conducted and they are, the slump test, the flowability test, the time set, and the heat of hydration. Hardened properties on the other hand, conducted tests on the compressive test at the age 7, 14, 28, 56 and 90 days, the absorption rate and the porosity parameter. The CLSM mix was designed based on a previous study which uses a 1.3 water-cement ratio. These CLSM mixtures were casted into moulds with the size of 100 mm x 100 mm x 100 mm. Every ratio was prepared in 28 cubes with different WPSA and OPC percentages corresponding to the total of 336 specimens. The aims of this research are first, to evaluate the potential of WPSA as a cementitious material to produce CLSM containing RCA, then, to formulate an optimum mix proportion of CLSM containing WPSA as a replacement binder material and RCA, and finally, to analyse and assess the effects of WPSA to the CLSM properties containing RCA. It has been found that the best design mix that achieves all CLSM properties is on S3 which is WPSA reacts as a replacement binder material containing RCA